2014
DOI: 10.1371/journal.pone.0106810
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the Impact of BDNF Val66Met Genotype on Serotonin Transporter and Serotonin-1A Receptor Binding

Abstract: BackgroundThe brain-derived neurotrophic factor (BDNF) Val66Met polymorphism (rs6265) may impact on the in-vivo binding of important serotonergic structures such as the serotonin transporter (5-HTT) and the serotonin-1A (5-HT1A) receptor. Previous positron emission tomography (PET) studies on the association between Val66Met and 5-HTT and 5-HT1A binding potential (BPND) have demonstrated equivocal results.MethodsWe conducted an imaging genetics study investigating the effect of Val66Met genotype on 5-HTT or 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…All healthy subjects from three previously reported samples collected between 2004 and 2016 for who genotypes for rs6265 and rs6295 were available were pooled for this analysis 7,35,41,45,46 . Due to the lack of a patient sample of adequate size to investigate genetic interaction, only healthy subjects were considered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All healthy subjects from three previously reported samples collected between 2004 and 2016 for who genotypes for rs6265 and rs6295 were available were pooled for this analysis 7,35,41,45,46 . Due to the lack of a patient sample of adequate size to investigate genetic interaction, only healthy subjects were considered.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning rs6265 of BDNF , several targets of the serotonergic system were investigated, including serotonin transporter (SERT), 5-HT 1A , and 2A receptor, as well as 5-HT 4 receptor binding. The less common A allele resulting in methionine was suggested to decrease 5-HT 1A receptor binding measured by free plasma concentration binding potential (BP F ) while other studies reported negative results based on BP ND 3537 . Recently, the A allele was also associated with increased SERT binding in a large cohort of healthy subjects, while earlier studies reported gender-dependent lower binding in A-carriers or no differences 35,36,38 .…”
Section: Introductionmentioning
confidence: 96%
“…This is a pooled sample derived from previous studies, however, all genetic data regarding rs6295 are unpublished. 48 , 49 , 50 , 51 , 52 , 53 Eighty-one subjects aged 18–65 years were enrolled in this neuroimaging genetics study with a cross-sectional design. Sixty-two healthy subjects (40 female) and 19 acutely depressed patients (6 female) diagnosed according to Structured Clinical Interview for DSM-IV type disorders (SCID I+II) were included.…”
Section: Methodsmentioning
confidence: 99%
“…70 In the human brain, the BDNF Met allele was associated with reduced 5-HT 1A binding in 1 study, 71 but not others. 72,73 In a recent study, 3 or more combined HTR1A and BDNF risk alleles associated increase 5-HT 1A receptor binding in cortical subregions. 74 In contrast, the COMT Val158Met rs4680 genotype oppositely altered the rs6295 association with interferon-induced depression.…”
Section: Genetic Interactionsmentioning
confidence: 99%